Can Relational Therapy be Appropriate for Clients with Schizophrenia?. Issue 4 (7th August 2016) - Walsh, Joseph
Abstract : Relational theory, a part of the psychodynamic tradition, assumes a positive worker–client relationship as the major factor in a client's psychological growth. It emphasises that intervention is a 'two-person' activity in which the subjective perspectives of both the client and practitioner combine to create a unique healing encounter. The goal of relational theory is to help clients overcome interpersonal problems that impair satisfactory functioning by developing a more cohesive sense of self through the clinical relationship. Given that people with schizophrenia often have major difficulties with social connection, relational therapy may hold promise for them as an intervention strategy, although the sometimes-intensive modality may heighten their anxiety, interpersonal boundary problems and other active symptoms. The purpose of this article is to consider whether relational therapy might be appropriate for some clients who have schizophrenia. Two case vignettes are utilised to illustrate the process.